2019
DOI: 10.4103/ijem.ijem_331_18
|View full text |Cite
|
Sign up to set email alerts
|

Body mass composition among underweight type 2 diabetes mellitus patients—A cross-sectional comparative study

Abstract: Background: Over the past decades, various epidemiological data have shown that the pattern and profile of diabetes mellitus in India are different. The present study was carried out with an aim to study body mass composition in underweight type 2 diabetics and to compare with the normal population. Materials and Methods: The cross-sectional comparative study was conducted between January 2015 and December 2016 and included 60 participants who were selected using the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…27 In the present study, obese, overweight and surprisingly underweight patients had a higher mean HbA1c compared to patients with normal body mass index, which could been attributed to the lifestyle factors including diet and physical activity and body mass composition. 28 The study results are in concurrence to the fact that smoking is a well-established risk factor for diabetes, which is responsible for the production of reactive oxygen species, protein glycation inflammatory molecules, β-cell dysfunction and end-organ protein damage. 29 In the present study, smokers had a higher HbA1c when compared to non-smokers, which was statistically significant (p<0.0001).…”
Section: Discussionsupporting
confidence: 81%
“…27 In the present study, obese, overweight and surprisingly underweight patients had a higher mean HbA1c compared to patients with normal body mass index, which could been attributed to the lifestyle factors including diet and physical activity and body mass composition. 28 The study results are in concurrence to the fact that smoking is a well-established risk factor for diabetes, which is responsible for the production of reactive oxygen species, protein glycation inflammatory molecules, β-cell dysfunction and end-organ protein damage. 29 In the present study, smokers had a higher HbA1c when compared to non-smokers, which was statistically significant (p<0.0001).…”
Section: Discussionsupporting
confidence: 81%
“…This study did not correlate with the study of Garg, Deepika Kumar et al (2019). 6 The cases included by Garg et al were basically underweight with BMI of <18.5 kg/m 2 . Similarly, study by Anjana et al reported that visceral and central abdominal fat was high among diabetic subjects as compared to nondiabetic subjects (P value = 0.005 and 0.011).…”
Section: Resultsmentioning
confidence: 99%
“…A study from India revealed that despite an insignificant correlation between HbA1c levels and BMI, there was a significant positive correlation between HbA1c and fat mass (r=0.452, p<0.001) in patients with T2D. 16 In addition, a prospective study from India also reported that centrally and peripherally obese subjects with dyslipidaemia had a significant association with HbA1c in T2D. 39 A community-based Korean cohort study demonstrated that, compared with people with a lower BF% (quintile 1), the risk for T2D significantly increased among those with a higher BF% (22.8% in men and 32.9% in women; ≥ quintile 4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from India have explored the relationship between BMI and BF%; however, there are gaps in evidence, as the studies had a limited sample size. [16][17][18][19][20][21][22][23] In this regard, large-scale registries can provide robust data on IP attributes in people with diabetes.…”
mentioning
confidence: 99%